Flouting Maxims in the Inside Out Film (2015); Pragmatics Study - Nastha Cecillia Firdaus; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2024)
The purpose of this research is to delve into the field of pragmatics, which involves understanding how meaning is conveyed by a speaker or writer and interpreted by a listener or reader, with a specific focus on instances of conversational flouting in the movie